Functional Activation-Informed Structural Changes during Stroke Recovery: A Longitudinal MRI Study. (24th October 2017) - Wu, Zhiyuan; Cheng, Lin; Yang, Guo-Yuan; Tong, Shanbao; Sun, Junfeng; Miao, Fei
Abstract : Objective . Neuroimaging studies revealed the functional reorganization or the structural changes during stroke recovery. However, previous studies did not combine the functional and structural information and the results might be affected by heterogeneous lesion. This study aimed to investigate functional activation-informed structural changes during stroke recovery. Methods . MRI data of twelve stroke patients were collected at four consecutive time points during the first 3 months after stroke onset. Functional activation during finger-tapping task was used to inform the analysis of structural changes of activated brain regions. Correlation between structural changes in motor-related activated brain regions and motor function recovery was estimated. Results . The averaged gray matter volume (aGMV) of contralesional activated brain regions and laterality index of gray matter volume ( L I G M V ) increased during stroke recovery, and L I G M V was positively correlated with Fugl-Meyer Index (FMI) at initial stage after stroke. The aGMV of bilateral activated brain regions was negatively correlated with FMI during the stroke recovery. Conclusion . This study demonstrated that combining the stroke-induced functional reorganization and structural change provided new insights into the underlying innate plasticity process during stroke recovery. Significance . This study proposed a new approach to integrate functional and structural information for investigating the innate plasticity after stroke.